Oral fluid-based biosensors: A novel method for rapid and noninvasive diagnosis - K Roja Lakshmi; Hasini Nelakurthi; A Sudarshan Kumar; Amrutha Rudraraju (Wolters Kluwer Medknow Publications, 2017)
In the recent times, chair-side/bed-side monitoring tests have gained importance over the routine laboratory tests as they are easier and faster to perform without requiring skilled personnel. Biosensors refer to such type of point-of-care devices that are developed to help in the early diagnosis, periodic monitoring, and treatment of disease. These devices utilize biological reactions for detecting and measuring a particular substance (analyte) of interest. Till date, blood has been the gold standard diagnostic fluid for various diseases. However, oral fluids such as saliva and gingival crevicular fluid offer advantages such as noninvasive collection of sample, smaller sample aliquots, easy storage and transportation, repeated sampling for monitoring over time, and greater sensitivity, making them an alternative clinical tool over serum and tissues for many biomedical diagnostic assays. This review highlights the use of oral fluid-based biosensors for diagnosis of caries, periodontitis, oral cancer, and various systemic diseases.